Linking Landfast Sea Ice Variability to Marine Ice Accretion at Hells Gate Ice Shelf, Ross Sea - Tison, J.-L.; Lorrain, R.; Bouzette, A.; Dini, M.; Bondesan, A.; Stiévenard, M. (HAL CCSD, 1998)
International audience